Clinical Features and Outcomes of Streptococcus anginosus Group Infective Endocarditis: A Multicenter Matched Cohort Study. (29th March 2021) - Escrihuela-Vidal, Francesc; López-Cortés, Luis Eduardo; Escolà-Vergé, Laura; De Alarcón González, Arístides; Cuervo, Guillermo; Sánchez-Porto, Antonio; Fernández-Hidalgo, Nuria; Luque, Rafael; Montejo, Miguel; Miró, José M; Goenaga, Miguel Ángel; Muñoz, Patricia; et al.
Abstract: Background: Although Streptococcus anginosus group (SAG) endocarditis is considered a severe disease associated with abscess formation and embolic events, there is limited evidence to support this assumption. Methods: We performed a retrospective analysis of prospectively collected data from consecutive patients with definite SAG endocarditis in 28 centers in Spain and Italy. A comparison between cases due to SAG endocarditis and viridans group streptococci (VGS) or Streptococcus gallolyticus group (SGG) was performed in a 1:2 matched analysis. Results: Of 5336 consecutive cases of definite endocarditis, 72 (1.4%) were due to SAG and matched with 144 cases due to VGS/SGG. SAG endocarditis was community acquired in 64 (88.9%) cases and affected aortic native valve in 29 (40.3%). When comparing SAG and VGS/SGG endocarditis, no significant differences were found in septic shock (8.3% vs 3.5%, P = .116); valve disorder, including perforation (22.2% vs 18.1%, P = .584), pseudoaneurysm (16.7% vs 8.3%, P = .108), or prosthesis dehiscence (1.4% vs 6.3%, P = .170); paravalvular complications, including abscess (25% vs 18.8%, P = .264) and intracardiac fistula (5.6% vs 3.5%, P = .485); heart failure (34.7% vs 38.9%, P = .655); or embolic events (41.7% vs 32.6%, P = .248). Indications for surgery (70.8% vs 70.8%; P = 1) and mortality (13.9% vs 16.7%; P = .741) were similar between groups. Conclusions: SAG endocarditis is an infrequent but serious condition that presents a prognosis similar to that of VGS/SGG. Abstract : In this multicenter matched cohort study, we found that Streptococcus anginosus group endocarditis follows a similar course to endocarditis caused by viridans or gallolyticus group streptococci, regarding valvular complications and prognostic variables such as indication for surgery and mortality.